THE CONCEPT OF THE INTEREST OF A LEGAL ENTITY AND ITS PLACE IN THE SYSTEM OF FIDUCIARY DUTIES OF A DIRECTOR - Ibrokhimov Azimjon Abdumumin ogli (Modern American Journals, 2026)
This article is dedicated to one of the pressing issues of corporate law – the emergence of fiduciary duties of a director in business entities and the clarification of the essence of the concept of "legal entity interest." The study provides a comparative analysis of the "Shareholder Primacy," "Pluralist Approach" (Stakeholder Theory), and "Enlightened Shareholder Value" approaches. Specifically, scientific proposals for improving the corporate legislation of Uzbekistan have been developed based on the UK Companies Act 2006 and other foreign experiences. The article highlights the relationship between the director's discretionary powers and the Business Judgment Rule.
Keywords: Fiduciary duties, interest of the legal entity, director's liability, shareholder primacy, stakeholders, enlightened shareholder value, corporate governance.